Argentinian Version of the Fear of COVID-19 Scale (FCV-19S): A Review of Possible Structural Models and its Relationship with Fear of Death - Furman, Hernan (2022)
During the pandemic caused by SARS-CoV-2, the Fear of COVID-19 Scale (FCV-19S) has become one of the main psycho-metric instruments used in research globally. The present study examined the psychometric properties of the Argentinian version of the FCV-19S. More specifically, the study analyzed and com-pared different possible models in order to determine which inter-nal structure fits better for the Argentinian FCV-19S. The sample comprised 505 adults from Argentina between 18 and 85 years (M = 45.44 years; SD = 17.08), of both genders (males = 33.5%; females = 66.5%). The results provided empirical support for a bi-factor structure with a general factor (α = .89) and two specific factors, that is, emotional response (α = .87) and physiological re-sponse (α = .83). Additionally, the associations between the FCV-19S and the Brief Fear of Death Scale (BFODS) provide evidence of validity related to other variables.